Direct Borylation of Primary CH Bonds in Functionalized Molecules by Palladium Catalysis - Zhang, Li-Sheng; Chen, Guihua; Wang, Xin; Guo, Qing-Yun; Zhang, Xi-Sha; Pan, Fei; Chen, Kang; Shi, Zhang-Jie (Angewandte Chemie International Edition, 2014)
Organoborane compounds are among the most commonly employed intermediates in organic synthesis and serve as crucial precursors to alcohols, amines, and various functionalized molecules. A simple palladium‐based system catalyzes the conversion of primary C(sp3)H bonds in functionalized complex organic molecules into alkyl boronate esters. Amino acids, amino alcohols, alkyl amines, and a series of bioactive molecules can be functionalized with the use of readily available and removable directing groups in the presence of commercially available additives, simple ligands, and oxygen (O2) as the terminal oxidant. This approach represents an economic and environmentally friendly method that could find broad applications. Crucial additives: A simple palladium‐based system catalyzes the conversion of primary C(sp3)H bonds in complex organic molecules into alkyl boronate esters. Amino acids, amino alcohols, alkyl amines, and a series of bioactive molecules that are modified with readily available directing groups are functionalized in the presence of commercially available additives, simple ligands, and oxygen as the terminal oxidant.